Alcohol consumption and harmful drinking Trends and social disparities across OECD countries - Devaux, Marion (OECD Publishing, 2015)
Harmful alcohol consumption is one of the leading causes of ill health and premature mortality worldwide. This paper illustrates trends and social disparities in alcohol consumption and harmful drinking in 20 OECD countries. Analyses are based on individual-level data from national health and lifestyle surveys. Alcohol consumption, on average, remained relatively stable in OECD countries over the past 20 years, but with significant variations between countries. However, a closer look at trends and patterns of consumption in specific population groups reveals a more complex picture. Young people are increasingly taking up harmful drinking. Women with high education and high socio-economic status are more likely to engage in harmful drinking than their less educated and less well-off counterparts, while the opposite is observed in men. Levels and patterns of alcohol consumption have an impact on labour market. Heavy alcohol consumption is associated with less employment opportunities, high wage penalties, and lower productivity, whereas light and moderate consumption are associated with positive labour market outcomes. By shedding light on some of the dimensions of alcohol consumption in OECD countries, this paper aims at contributing to the design of appropriate health policies to prevent alcohol-related harms. The findings presented in the paper provide a basis for a quantitative assessment of the impacts of alternative policy options, and may contribute to a better targeting of such policies
Keywords: Social Issues/Migration/Health